Complex development alternatives in South-Muntenia region: Prospective assessments - Sorinel Ionel Bucur (Agrarian Economy and Rural Development - Realities and Perspectives for Romania. 8th Edition of the International Symposium, November 2017, Bucharest, 2017)
To raise the issue of the complex development of a zone where the agricultural production is the prevailing economic activity implies a certain difficulty, induced by the natural question: how can pluri-activity be generated in a predominantly mono-active rural area? Even if, at first sight, the issue could be considered relatively marginal, in reality, at least two essential "agents": agriculture, as such, and the remaining national economy have participated to the complex development of the rural area. Agriculture, because when it reaches performance, it becomes capable to generate surplus supply compared to the local consumption needs, available for re-distribution to other deficit areas or for processing. The national economy, because it generates alternative incomes for the surplus agricultural population through various non-agricultural activities developed in the rural area. Starting from the premise that regional development, in general, and rural development, in particular, takes place almost exclusively through local initiatives, we consider that by identifying certain production intensification opportunities in crops and livestock species that have favorable conditions in the counties from South-Muntenia region, we can shape the main pillars for the complex development at regional level. From the methodological point of view, the approach is based on public statistical information, using well-known statistical methods for processing the information, of comparison or structural type, the results being mainly presented under table form. The information support necessary for the development of the present approach was based on data supplied mainly by the National Institute of Statistics, through the Tempo-Online database.
Keywords: R10; R11; R12; 330; sustainable development; alternatives; criteria